1978
DOI: 10.1111/j.1432-1033.1978.tb12741.x
|View full text |Cite
|
Sign up to set email alerts
|

Translation of MS2 RNA in vitro in the Absence of Initiation Factor IF‐3

Abstract: An Escherichia coli cell‐free translational system, deprived of initiation factor IF‐3, has been used to study the role of the factor in protein synthesis. In this system, 30‐S ribosomal subunits are preincubated together with MS2 phage RNA in a small volume in the presence of 10 mM Mg(Ac)2; the missing components required for protein synthesis are then added and assembly of elongating ribosomes is allowed to occur. This stepwise assembly process prermits formation of functional complexes which can carry out p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Most of the evidence from procaryotic systems indicates that recognition of initiation sites in mRNA is an intrinsic property of the ribosome, as first revealed by Lodish's mixing experiments with ribosomes and factors from E. coli and Bacillus stearothermophilus (274,275; see discussion below). In support of that conclusion, studies using washed (i.e., factor-free) ribosomes from E. coli revealed that the low level of binding obtained in the absence of IF-3 occurs at the authentic initiation sites in coliphage mRNAs (458,553). Nevertheless, bacterial initiation factors-particularly IF-3-influence the relative utilization of initiation sites by differentially stabilizing the binding of ribosomes to mRNAs.…”
Section: Soluble Protein Factors Required For Initiationmentioning
confidence: 87%
See 1 more Smart Citation
“…Most of the evidence from procaryotic systems indicates that recognition of initiation sites in mRNA is an intrinsic property of the ribosome, as first revealed by Lodish's mixing experiments with ribosomes and factors from E. coli and Bacillus stearothermophilus (274,275; see discussion below). In support of that conclusion, studies using washed (i.e., factor-free) ribosomes from E. coli revealed that the low level of binding obtained in the absence of IF-3 occurs at the authentic initiation sites in coliphage mRNAs (458,553). Nevertheless, bacterial initiation factors-particularly IF-3-influence the relative utilization of initiation sites by differentially stabilizing the binding of ribosomes to mRNAs.…”
Section: Soluble Protein Factors Required For Initiationmentioning
confidence: 87%
“…Several of the factors bind to both free ribosomal subunits and mRNA, but it has been difficult to evaluate the functional significance of the latter complexes. Bacterial component IF-3, for example, binds to phage mRNA (209), but the preformed complex of IF-3 and coliphage MS2 RNA was inert when subsequently tested for translation in the presence of anti-IF-3 antibodies (553). Several eucaryotic initiation faetors also bind to mRNA, including eIF-2 (216) and eIF-3 (182,512); however, neither of those interactions is specific for mRNA (70,181,512).…”
Section: Soluble Protein Factors Required For Initiationmentioning
confidence: 99%
“…Furthermore, our results suggest a direct competition for the 3′ end between the replicase and IF3 because increasing concentrations of either the replicase or the substrate RNA compensated for the inhibitory effect of IF3. Notably, MS2 gene expression was also shown to be completely independent from IF3, unlike for E. coli host proteins 53 . Thus, replication and translation of MS2 genomes seem to be well adapted to conditions under which IF3 levels are minimal, such as it was reported for E. coli cells that have reached stationary phase 54 .…”
Section: Discussionmentioning
confidence: 99%
“…[for reviews see Lodish (1976), Grunberg-Manago & Gros (1977), and Revel (1977)], although under certain conditions this protein has been found to be dispensable (Zipori et al, 1978). The degree of initiation stimulation by IF3 appears to correlate with the extent of secondary structure present in the initiation region of the mRNA, regardless of whether the mRNA is synthetic or naturally occurring (Lodish, 1976;Revel, 1977).…”
mentioning
confidence: 99%